If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(y+2)*4=64
We move all terms to the left:
(y+2)*4-(64)=0
We multiply parentheses
4y+8-64=0
We add all the numbers together, and all the variables
4y-56=0
We move all terms containing y to the left, all other terms to the right
4y=56
y=56/4
y=14
| 4(x-2)-3x=1.7 | | 5a+3=25 | | 6b+18=8b+6 | | 9x2X16=0 | | -8v-48=2(v-4) | | 9x2•16=0 | | -8v48=2(v-4) | | 9x^2x16=0 | | f(20)=2(20)^2+5(20)-17 | | 11a−4=40 | | 11m−4=40 | | 3/4+m=-5/4 | | 4x+15=-2x+39 | | 2-2s=3/2s+13 | | 7x-2=x-26 | | 1÷x+3=5 | | 2x+3=-5x+31 | | -2x+16=-3x+11 | | 2x-16=4x-36 | | -5x-12=-x-16 | | 1/4k+2=1/2k-3 | | -3x+21=42 | | 11x+11=5x-19 | | -2x+16=-4x+10 | | -2x-16=-34 | | 2x+1x=-2+9 | | -x+20=24 | | Tn=2n–1 | | -5x+19=-3x+11 | | 7x+84/3=7 | | 10x-2/4=7 | | (x/2)+10=5·4 |